SINOPE – SEBAGAI MEDIA PEMBELAJARAN INOVASI PEMBELAJARAN BIOLOGI BERBASIS WEBSITE PADA PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS PGRI SUMATERA BARAT - Ami Anggraini Samudra; Ade Dewi Maharani (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2023)
One of the course achievements in the Inovasi Pembelajaran Biologi course is that students are able to design a variety of biology learning innovations, especially those based on technology. However, in reality students still have not utilized technology to the fullest and there has not been clear innovation in the use of technology in the various innovations that students have designed. So this research aims to develop a web-based information system as a learning medium that will be used during the learning process and at the same time as a direct example of the application of the use of Information, Media and Technology Skills in learning innovation. This research is a development research that focuses more on software development. System development is carried out using an iterative model and beta testing. The results of this study are in the form of an information system called SINOPE with the results of beta testing for each indicator, namely: design 91.7%, menu 90%, content 83.3%, ease of use 93.3%, usability 91.7%, average subject responses research on SINOPE is 90% with a very good category.